2023
DOI: 10.1542/peds.2022-061083
|View full text |Cite
|
Sign up to set email alerts
|

Care Coordination Programs for Infants With Complex Conditions: A Systematic Review

Abstract: CONTEXT: Care coordination programs are becoming more widely available for children with complex conditions, yet we lack an understanding of programs available to infants and their benefits. OBJECTIVE: To summarize characteristics and outcomes associated with care coordination programs for infants with complex conditions. DATA SOURCES: Electronic search of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Many programs began using telehealth platforms for follow-up care during the COVID-19 pandemic [27,28]. A recent systematic review found that care coordination for infants with complex care needs reduces costs for families and health systems and leads to improved care quality [29].…”
Section: Overview Of Clinical High-risk Infant Follow-up Carementioning
confidence: 99%
“…Many programs began using telehealth platforms for follow-up care during the COVID-19 pandemic [27,28]. A recent systematic review found that care coordination for infants with complex care needs reduces costs for families and health systems and leads to improved care quality [29].…”
Section: Overview Of Clinical High-risk Infant Follow-up Carementioning
confidence: 99%